Internet technology, Crm and customer loyalty: customer retention and satisfaction perspective - Nikhashemi, Seyed Rajab; Paim, Laily; Haque, Ahasanul; Khatibi, Ali; Tarofder, Arun Kumar (IDOSI Publications, 2013)
The purpose of this study is to investigate the effect of internet technology on customer loyalty. Besides, further discussion of the relationships among internet technology, customer satisfaction, customer retention and loyalty are presented. This study has also given more insight into the application of various Internet technologies that can be utilized in Customer Relationship Management (CRM) in order to build a profitable customer-centric business model. A survey instrument was used to examine the relationships in the proposed model. The collected primary surveys (n = 288) are conducted to test the relationships among the four dimensions expressed in the proposed structural model; therefore, regression analysis as well as correlation were run to analyze the data. The results demonstrate that Internet technology does not only improve the customer service, but more importantly, it can deliver value to the customers through which retention rate and customer loyalty will be enhanced. Moreover, Customer satisfaction has strong relationship with customer retention, but poor relationship with customer loyalty. On the other hand, customer retention has significant relationship with customer loyalty. The obtained results indicate that customer satisfaction strongly influences customer retention, whereas customer retention can affect customer loyalty.